Clinical, Immunological, and Molecular Features of Severe Combined Immune Deficiency: A Multi-Institutional Experience From India - Vignesh, Pandiarajan; Rawat, Amit; Kumrah, Rajni; Singh, Ankita; Gummadi, Anjani; Sharma, Madhubala; Kaur, Anit; Nameirakpam, Johnson; Jindal, Ankur; Suri, Deepti; Gupta, Anju; Khadwal, Alka; et al. (Frontiers in Immunology, 2021)
Background: Severe Combined Immune Deficiency (SCID) is an inherited defect in lymphocyte development and function that results in life-threatening opportunistic infections in early infancy. Data on SCID from developing countries are scarce. Objective: To describe clinical and laboratory features of SCID diagnosed at immunology centres across India. Methods: A detailed case proforma in an Excel format was prepared by one of the authors (PV) and was sent to centres in India that care for patients with primary immunodeficiency diseases. We collated clinical, laboratory, and molecular details of patients with clinical profile suggestive of SCID and their outcomes. Twelve (12) centres provided necessary details which were then compiled and analyzed. Diagnosis of SCID/ combined immune deficiency (CID) was based on 2018 European Society for Immunodeficiencies working definition for SCID. Results: We obtained data on 277 children; 254 were categorised as SCID and 23 as CID. Male-female ratio was 196:81. Median (inter-quartile range) age of onset of clinical symptoms and diagnosis was 2.5 months (1, 5) and 5 months (3.5, 8), respectively. Molecular diagnosis was obtained in 162 patients - IL2RG (36), RAG1 (26), ADA (19), RAG2 (17), JAK3 (15), DCLRE1C (13), IL7RA (9), PNP (3), RFXAP (3), CIITA (2), RFXANK (2), NHEJ1 (2), CD3E (2), CD3D (2), RFX5 (2), ZAP70 (2), STK4 (1), CORO1A (1), STIM1 (1), PRKDC (1), AK2 (1), DOCK2 (1), and SP100 (1). Only 23 children (8.3%) received hematopoietic stem cell transplantation (HSCT). Of these, 11 are doing well post-HSCT. Mortality was recorded in 210 children (75.8%). Conclusion: We document an exponential rise in number of cases diagnosed to have SCID over the last 10 years, probably as a result of increasing awareness and improvement in diagnostic facilities at various centres in India. We suspect that these numbers are just the tip of the iceberg. Majority of patients with SCID in India are probably not being recognised and diagnosed at present. Newborn screening for SCID is the need of the hour. Easy access to pediatric HSCT services would ensure that these patients are offered HSCT at an early age